Kondisi Sosial Ekonomi Masyarakat Nelayan di Kampung Bianci Kawasan Kepulauan Raja Ampat Provinsi Papua Barat - Himawan, Bismar; Yahya, Nurfadila; Awaluddin, Awaluddin; Jamil, Khairul (Fakultas Perikanan UCM, 2024)
This study aims to analyse the socio-economic conditions of the fishing community in Bianci Village, Raja Ampat Regency, Southwest Papua Province. A descriptive quantitative method was used, with data collected through observation, interviews, and questionnaires involving 10% of the total households. The results show that most fishermen have only completed elementary education (64%), are in their productive age, and support relatively large families. Public facilities, consisting of one elementary school, one mosque, and a single posyandu (integrated health post) with restricted service frequency, are limited. Fishing operations utilise simple wooden boats with outboard engines and traditional nylon hand lines, producing an average catch of 10–15 kg per trip, predominantly groupers. The average monthly income of fishermen reaches IDR 6,018,000, exceeding the regional minimum wage of Southwest Papua, indicating a relatively prosperous economic condition. Despite limited infrastructure, the economic potential of the fishing community remains promising and should be supported through integrated coastal empowerment programs.